PUBLIC OWNER WITH BUSINESS DELIVERY MODE IN CHINA: CASE STUDY OF THE SHANGHAI PUBLIC BUS SYSTEM. (March 2014) - WANG, Huanming; WARNER, Mildred E.; TIAN, Yuanhong; ZHU, Dajian; Marra, A.; Cruz, N.F.; Fecher, F.; Marques, R.C.
ABSTRACT Since 2008, some of China's municipal governments have reversed the privatization of market‐led reform in the bus transport field. But this reversal is not a return to the direct public monopoly delivery model of the past. Instead the new structure is a hybrid of public control with business delivery. This mixed model attempts to balance government, market and social groups. This mode is a contracting network where government plays a lead role to organize the stakeholders to achieve common goals. This paper uses the Shanghai municipality bus service as a case to illustrate this new mode. It argues that the contract between government and operators and the participation of social groups helps balance the control of the government. This mixed network mode of management reduces information asymmetries and promotes shared goals to ensure a higher quality, more responsive service. While not a mixed firm in the sense found in Europe, this mixed public‐public contracting network in China offers insights into the core challenges mixed firms have emerged to address.